The faint end of the 250μm luminosity function at z< 0.5 - Wang, L.; Norberg, P.; Bethermin, M.; Bourne, N.; Cooray, A.; Cowley, W.; Dunne, L.; Dye, S.; Eales, S.; Farrah, D.; Lacey, C.; Loveday, J.; et al. (EDP Sciences, 2016)
Aims. We aim to study the 250 μm luminosity function (LF) down to much fainter luminosities than achieved by previous efforts. Methods. We developed a modified stacking method to reconstruct the 250 μm LF using optically selected galaxies from the SDSS survey and Herschel maps of the GAMA equatorial fields and Stripe 82. Our stacking method not only recovers the mean 250 μm luminosities of galaxies that are too faint to be individually detected, but also their underlying distribution functions. Results. We find very good agreement with previous measurements in the overlapping luminosity range. More importantly, we are able to derive the LF down to much fainter luminosities (~ 25 times fainter) than achieved by previous studies. We find strong positive luminosity evolution L*250(z)∝(1+z)4.89±1.07 and moderate negative density evolution Φ*250(z)∝(1+z)-1.02±0.54 over the redshift range 0.02 <z< 0.5.